Combination Blockade of the IL6R/STAT-3 Axis with TIGIT and Its Impact on the Functional Activity of NK Cells against Prostate Cancer Cells - S. González-Ochoa; M. C. Tellez-Bañuelos; A. S. Méndez-Clemente; A. Bravo-Cuellar; G. Hernández Flores; L. A. Palafox-Mariscal; J. Haramati; E. J. Pedraza-Brindis; K. Sánchez-Reyes; P. C. Ortiz-Lazareno (Journal of Immunology Research)
Background/Aims. Prostate cancer (PCa) is one of the neoplasms with the highest incidence and mortality rate in men worldwide. Advanced stages of the disease are usually very aggressive, and most are treated with chemotherapeutic drugs that generally cause side effects in these patients. However, additional therapeutic targets such as the IL6R/STAT-3 axis and TIGIT have been proposed, mainly due to their relevance in the development of PCa and regulation of NK cell-mediated cytotoxicity. Here, we evaluate the effect of inhibitors directed against these therapeutic targets primarily via an analysis of NK cell function versus prostate cancer cells. Methods. We analyzed the secretion of cytokines, chemokines, and growth factors in 22Rv1, LNCaP, and DU145 cells. In these cells, we also evaluated the expression of NK ligands, IL6R, STAT-3, and phosporylated STAT-3. In NK-92 cells, we evaluated the effects of Stattic (Stt) and tocilizumab (Tcz) on NK receptors. In addition, we assessed if the disruption of the IL6R/STAT-3 pathway and blockade of TIGIT potentiated the cytotoxicity of NK-92 cells versus DU145 cells. Results. DU145 abundantly secretes M-CSF, VEGF, IL-6, CXCL8, and TGF-β. Furthermore, the expression of CD155 was found to increase in accordance with aggressiveness and metastatic status in the prostate cancer cells. Stt and Tcz induce a decrease in STAT-3 phosphorylation in the DU145 cells and, in turn, induce an increase of NKp46 and a decrease of TIGIT expression in NK-92 cells. Finally, the disruption of the IL6R/STAT-3 axis in prostate cancer cells and the blocking of TIGIT on NK-92 were observed to increase the cytotoxicity of NK-92 cells against DU145 cells through an increase in sFasL, granzyme A, granzyme B, and granulysin. Conclusions. Our results reveal that the combined use of inhibitors directed against the IL6R/STAT-3 axis and TIGIT enhances the functional activity of NK cells against castration-resistant prostate cancer cells.